2015
DOI: 10.1177/1934578x1501001118
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Tannins – from in Vitro Studies to Clinical Trials

Abstract: Tannins are considered as valuable plant secondary metabolites providing many benefits for human health. In this review information was gathered about bioactivity in vitro and in vivo, as well as about conducted clinical trials. The literature research was based on ScienceDirect, Scopus, and Cochrane databases and presents a wide range of tested activities of tannins. The described clinical trials verify laboratory tests and show the effective health benefits taken from supplementation with tannins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 84 publications
5
80
0
8
Order By: Relevance
“…In some instances, some procyanidins such as procyanidin B1 and procyanidin B3 have been recognized to be stronger antioxidants than ascorbic acid or α‐tocopherol (Iglesias et al, ). These results observed in vitro have also been confirmed by several in vivo studies on animal models (Kancheva and Kasaikina, ; Nile and Park, ; Sieniawska, ; Skrovankova et al, ).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…In some instances, some procyanidins such as procyanidin B1 and procyanidin B3 have been recognized to be stronger antioxidants than ascorbic acid or α‐tocopherol (Iglesias et al, ). These results observed in vitro have also been confirmed by several in vivo studies on animal models (Kancheva and Kasaikina, ; Nile and Park, ; Sieniawska, ; Skrovankova et al, ).…”
Section: Introductionsupporting
confidence: 77%
“…Despite their abundance in our diet (estimated daily intake 0.1–0.5 g), tannins have received little attention, probably due to their polymeric nature and high structural complexity (Serrano et al, ). In recent years, considerable attention has been paid to proanthocyanidins and their monomers due to the potential beneficial effects on human health, including immunomodulatory, anti‐inflammatory, anticancer, antioxidant, cardio‐protective and antithrombotic properties (Nile and Park, 2014; Smeriglio et al, ; Sieniawska, ). However, to assess their precise role in human health, it is essential to gather further knowledge on their pharmacological and toxicological behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proanthocyanidins have also been observed to maintain the oxidative balance by scavenging hydroxyl, superoxide, and peroxyl radicals in vivo (Georgiev, Ananga, & Tsolova, 2014). A clinical study showed decreased free radical production after 18 volunteers consumed proanthocyanidins-rich chocolate (Sieniawska, 2015). (c) Antiobesity activity: various animal studies have reported the antiobesity effects of proanthocyanidins in many aspects, such as inhibiting the activity of lipase, promotion of glucose metabolism, activation of lipid metabolism, promotion of energy expenditure, and inhibition effect of energy intake, targeting the hypothalamus (Ibars et al, 2017;Salvado, Casanova, Fernandez-Iglesias, Arola, & Blade, 2015;Zhang, Chen, Wei, Chen, & Ye, 2017).…”
Section: Health Benefits Of Proanthocyanidinsmentioning
confidence: 99%
“…More recently, it has been identified as suitable for treatment of abrasions. It has been linked as having antitumor, antihypertensive, antibacterial, antiviral, antibiofilm, and neuroprotective properties [202]. However, tannic acid has also been shown to be hepatotoxic [203] and cytotoxic to mouse fibroblasts at a concentration higher than 100 μM.…”
Section: Pkc Modulation By Polyphenolsmentioning
confidence: 99%